Biomarkers of diabetic retinopathy. (March 2014) - Cunha-Vaz, José; Ribeiro, Luísa; Nunes, Sandrina; Lobo, Conceição
SUMMARY  Diabetic retinopathy (DR) progresses over time at different rates in different individuals, with only a limited number of patients developing significant vision loss owing to the two major vision-threatening complications of DR, clinically significant macular edema and proliferative retinopathy. Good metabolic control is important to prevent and delay disease progression, but whereas some patients develop vision-threatening DR complications and vision loss despite good control, others escape vision loss even with poor metabolic control. Microaneurysm turnover has been validated as a prognostic biomarker of development of clinically significant macular edema. Other good candidates for prognostic biomarkers of DR are subclinical macular edema identified by optical coherence tomography and multifocal electroretinography. Percentage retinal thickness decrease is also a good candidate for a predictive biomarker for visual acuity response to anti-VEGF therapy. Although other candidates for systemic biomarkers have been proposed, hemoglobin A1c remains the only confirmed systemic prognostic biomarkers of DR progression. The availability of prognostic and predictive biomarkers of DR associated with generalized screening creates the conditions for preventive and personalized management of DR.